An Empirical Analysis of Fiscal Adjustments - Westcott, Robert (IMF Working Papers; Working Paper ;, 1996)
This study uses the fiscal expansion and consolidation experiences of the industrial countries over the period 1970 to 1995 to examine the interplay between fiscal adjustments and economic performance. A key finding is that fiscal consolidation need not trigger an economic slowdown. Fiscal consolidation that concentrates on the expenditure side, and especially on transfers and government wages, is more likely to succeed in reducing the public debt ratio than tax-based consolidation. Also, the greater the magnitude of the fiscal consolidation, the more likely it is to succeed in reducing the debt ratio.